Frog meets dog - Trasler, Janee (New York : Scholastic Inc., 2020)
Dog would like to play with the three frogs he has met, but he is not good at their games of hopping and leaping--but when he chases away a bear the frogs decide to welcome him into their play time.
Ages 4-6
K to Grade 3
Keywords: Frogs -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Play -- Juvenile fiction; Frogs -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Play -- Fiction; Readers (Publications); Picture books; Animal fiction